2016
DOI: 10.1007/s11010-016-2724-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycated LDL increase VCAM-1 expression and secretion in endothelial cells and promote monocyte adhesion through mechanisms involving endoplasmic reticulum stress

Abstract: Type 2 Diabetes Mellitus is a worldwide epidemic, and its atherosclerotic complications produce morbidity and mortality in affected patients. It is known that the vascular cell adhesion molecule-1 (VCAM-1) levels are increased in the sera of diabetic patients. Our aim was to investigate the impact of the endoplasmic reticulum stress (ERS) in VCAM-1 expression and secretion in human endothelial cells (HEC) exposed to glycated low-density lipoproteins (gLDL). The results showed that 24 h incubation of HEC with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
8
29
0
Order By: Relevance
“…It is well known that the inflammatory stress is directly linked to the oxidative stress, well known for its contribution to the diabetic complications . Using NAC, a wide spectrum antioxidant, we have previously shown and now confirm that inhibition of the oxidative stress diminishes VCAM‐1 secretion from gLDL‐ exposed HEC . In addition, we now show that CRP secretion in gLDL‐exposed HEC is also inhibited by NAC, in good agreement with a previous published study in HEC incubated with electronegative LDL .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is well known that the inflammatory stress is directly linked to the oxidative stress, well known for its contribution to the diabetic complications . Using NAC, a wide spectrum antioxidant, we have previously shown and now confirm that inhibition of the oxidative stress diminishes VCAM‐1 secretion from gLDL‐ exposed HEC . In addition, we now show that CRP secretion in gLDL‐exposed HEC is also inhibited by NAC, in good agreement with a previous published study in HEC incubated with electronegative LDL .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, CAF decreases the secretion of VCAM‐1 and MCP‐1 induced by gLDL in HEC, the results confirming previous data showing that CAF decreases inflammation in HEC incubated with resistin or high glucose or in a hyperhomocysteinemia in vivo model by attenuating NF‐kB signaling . We have previously shown that the secretion of VCAM‐1 and MCP‐1 is stimulated in gLDL‐exposed HEC by activation of NF‐kB . The addition of CAF in the culture medium of gLDL‐exposed HEC decreased the phosphorylation of p65 subunit of NF‐kB (data not shown), confirming the latter as an important molecular mechanism for the observed anti‐inflammatory properties of CAF.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations